The Sport Co-Curricular as Social Skill Reinforcement for Students of Apprenticeship Program - Indroasyoko, Narwikant; Muhammad, Achmad; Sabarini, Sri Santoso (Department of Physical Education, Sport, Health and Recreation, 2020)
The aim of this study is to gain deep knowledge about the benefit of co-curricular program both team sport and individual sport and to find out the influencing factors in following co-curricular activity, as social skill reinforcement for intern students, so concept and strategy are acquired to create Human Resources who are professional, healthy physically and mentally to face the era of revolution 4.0. The study result shows that implementation of co-curricular in campus greatly affects student’s learning system when they do on -the- job training in apprentice location. Students can find new things that occur in social interaction such as relation among students, student with mentor, student with employee in apprentice place or inside campus so students have more ethics in learning and in daily social intercourse. The obstacles among others are students do not get mentor in campus who has guidance skill profession, mentor who has trouble to equalize problem with material and time limitation, infrastructure which is less conducive in the process of co-curricular program implementation.